Global research trends in building-integrated photovoltaics: a bibliometric analysis (1971-2022) - Tambunan, Handrea Bernando; Digwijaya, Wigas; Nurfanani, Achmad (Bulletin of Electrical Engineering and Informatics, 2025)
The number of academic publications in the building-integrated photovoltaics (BIPV) field has rapidly grown. Most published articles focus on a specific topic, such as mathematical model, solar architecture design, photovoltaic effect, solar cell, grid-connected, efficiency, performance assessment, economic analysis, optimization, and others with broader focus areas. This work focuses on BIPV research with bibliometric analysis through documents, cited references, authors, affiliations, countries, funding sponsors, sources, words, and conceptual structure based on the Scopus-indexed database between 1971 and 2022. The result shows that BIPV research constantly grows annually with strong collaboration authorship. China is the most relevant country with the top affiliation and funding sponsor to support the BIPV research. The terms conjugated polymers, photovoltaic properties, and organic polymer are identified as niche themes. On the other hand, the terms of conversion efficiency, perovskite, photovoltaic devices, solar cells, efficiency, and photoelectrochemical cell clusters are emerging themes. In the future, BIPV research will move towards microgrids, energy, performance, energy management systems, and energy efficiency issues. The finding will also provide researchers and organizations with a comprehensive understanding of BIPV research areas and new directions for future research.